(untitled) (Research, Society and Development, 2020)
Introduction: Breast cancer is among the most common tumors in women. Conventional imaging methods for evaluating breast nodules (USG and mammography) show high rates of sensitivity, but they also have a large number of false positives. In this sense, several authors have described that elastography can assist in this process. It is a relatively recent tool that is available on some USG devices and evaluates the deformity of the tissue in response to an imposed compression, providing information about the elasticity / stiffness of the tissue. With this in mind, the objective of the present study is to evaluate the effectiveness of elastography to differentiate the hitological types of nodules and to compare their effectiveness with the BI-RADS classification. Method: This is a prospective cohort that performed standard ultrasound and strain elastography in patients with breast nodules. Biopsy was performed when necessary. The values ​​of the percentage of rigid area (RA), identified by elastography, were compared between the different classes of the traditional BI-RADS classification, as well as were compared between the benign and malignant groups, characterized from the histopathological findings. Results: In all, 128 female patients were included in the study. It was demonstrated that the BI-RADS groups 4B, 4C and 5 present higher values ​​of percentage of RA. There was a statistically significant difference between the% RA in benign and malignant tumors. Conclusions: The findings of elastography associated with the calculation of a rigid area can increase the diagnostic probability of breast cancer, and can be used in routine breast assessment.